การสร้างและศึกษาลักษณะของวัสดุเชิงแบนเดอร์วาลส์ที่ประกอบจากโมลิบดีนัมไดซัลไฟด์ - ปฐมพร ชายเขา (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
Molybdenum disulfide (MoS₂) is one of the most studied 2D material from family of transition metal dichalcogenides (TMDs). It possesses many fascinating properties such as its high transparency, super strong, durable, flexible, and super thin. Monolayer MoS₂ is a semiconductor with a direct bandgap of 1.8 eV very high compared to other semiconducting 2D materials. All of the aforementioned properties are essential for many applications, such as energy conversion and storage, wearable electronics and optoelectronics. In addition, stacking of 2D materials to create van der Waals heterostructure especially the stacking of two single-layer flakes of MoS₂ may be able to provide new functionalities. In this thesis, we attempt to fabricate and study two type of 2D van der Waals heterostructure based on MoS₂. First, Raman spectrum of twisted bilayer (tMoS₂) is fabricated using pick-up technique and its Raman spectrum is investigated. The peak frequency difference between the two Raman modes of tMoS₂ has a value between single-and bi-layer MoS2 and the peak intensity of tMoS2 is lower than that of bilayer MoS₂. This indicates that the tMoS₂ has different characteristics from its single-and bi-layer counterparts. Second, we fabricated field effect transistor from single layer MoS₂/BN van der Waals heterostructure. We measure two-probe electrical conductivity and a function of mobility and find mobility of 2.25 cm⁻²V⁻¹s⁻¹ at room temperature.